Uji Efektifitas Dinding Ruangan Panoramik Instalasi Radiologi RSUD Prof. Dr. MA Hanafiah SM Batusangkar Menggunakan TLD-100 - Dila Nelvo Dasril; Nerifa Dewilza (Physics Education Research Journal, 2020)
Research on the effectiveness of panoramic room walls has been carried out in the Radiology Installation of Prof. Dr. MA Hanafiah SM Batusangkar. This study aims to determine the effectiveness of the panoramic room walls in absorbing radiation emitted by panoramic aircraft, as well as knowing the safety level of the room around the panoramic inspection room in accordance with the dose limit values of workers and the general public. This type of research is a quantitative research by taking direct measurements. The research was conducted by measuring the radiation dose at six points of the panoramic room wall using a radiation measuring instrument, namely TLD-100. The results showed that the effectiveness of the walls was only able to absorb radiation less than 90%, with the shield category on the walls that was not good enough to withstand radiation. Therefore, it is necessary to renovate the panoramic room walls in accordance with safety standards.